Significant Difference of Immune Cell Fractions and Their Correlations With Differential Expression Genes in Parkinson’s Disease - Huang, Yilin; Liu, Huisheng; Hu, Jiaqi; Han, Chongyin; Zhong, Zhenggang; Luo, Wei; Zhang, Yuhu; Ling, Fei (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is the second most neurodegenerative disease in the world. T cell infiltration in the central nervous system (CNS) has provided insights that the peripheral immune cells participate in the pathogenesis of PD. However, the association between the peripheral immune system and CNS is remained to be elucidated. Here, we analyzed an incorporative substantial nigra expression data as well as another blood expression data using the CIBERSORT to obtain the 22 immune cells fraction and then explored the molecular function to identify the potential key immune cell types and genes of PD. We observed the proportions of naïve CD4 T cells, gamma delta T cells, resting NK cells, neutrophils in the blood, and regulatory T cells (Tregs) in the substantial nigra were significantly different between PD patients and healthy controls (HC). We identified p53-induced death domain protein 1 (PIDD1) as the hub gene of a Parkinson’s disease-related module. The set of neuron-specific genes was significantly different between PD and HC, and genes in the neuron-related module were enriched in the biological process about mitochondria and synapses. These results suggested that the fractions of naïve CD4 T cells, gamma delta T cells, resting natural killer (NK) cells, as well as neutrophils, may be used as a combined diagnostic marker in blood and Tregs in substantial nigra may be a potential therapeutic design target for PD.